2011
DOI: 10.3390/s111211774
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Imaging Methods for Nondestructive Evaluation Applications

Abstract: Electromagnetic nondestructive tests are important and widely used within the field of nondestructive evaluation (NDE). The recent advances in sensing technology, hardware and software development dedicated to imaging and image processing, and material sciences have greatly expanded the application fields, sophisticated the systems design and made the potential of electromagnetic NDE imaging seemingly unlimited. This review provides a comprehensive summary of research works on electromagnetic imaging methods f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 109 publications
(111 reference statements)
0
38
0
Order By: Relevance
“…The outside pole is set at O 2 , the centre of spherical surface Γ 2 . The solution to the Laplace Equation (6) in the valid domain is given as follows [4,7,8]: leftW=A+l=1Nlrilfalse(AilPlfalse(cosθifalse)+m=1lPlm(cosθi)(Ailmcosmαi+Bilmsinmαi)false)+p=1Np[Aoprop+l=1Nopritalicopfalse(l+1false)false(AitalicoplPlfalse(cosθitalicopfalse)+m=1lPlm(cosθi)(Aoplmcosmαop+Boplmsinmαop))left=k=1NαkUkwhere ri=|rtrue→ri1true→|, ri1true→…”
Section: Electromagnetic Modeling Of the Sensormentioning
confidence: 99%
“…The outside pole is set at O 2 , the centre of spherical surface Γ 2 . The solution to the Laplace Equation (6) in the valid domain is given as follows [4,7,8]: leftW=A+l=1Nlrilfalse(AilPlfalse(cosθifalse)+m=1lPlm(cosθi)(Ailmcosmαi+Bilmsinmαi)false)+p=1Np[Aoprop+l=1Nopritalicopfalse(l+1false)false(AitalicoplPlfalse(cosθitalicopfalse)+m=1lPlm(cosθi)(Aoplmcosmαop+Boplmsinmαop))left=k=1NαkUkwhere ri=|rtrue→ri1true→|, ri1true→…”
Section: Electromagnetic Modeling Of the Sensormentioning
confidence: 99%
“…Imaging piecewise homogeneous objects is of interest in various applications in non-destructive testing [4] and subsurface sensing [5]. Several spatial smoothing techniques have been proposed to enhance edges in nonlinear inverse scattering algorithms, e.g., L1-norm total variation (TV) regularization [6], edge-preserving regularization [7] with weighted L2-norm TV [8] and with various potential functions [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…The more consolidated applications perhaps are those related to the use of ground penetrating radar, but a lot more are at present used or in advanced state of development. For example, it has been suggested that microwave imaging could be successfully used as a diagnostic technique in several areas, including civil and industrial engineering [3][4][5], nondestructive testing and evaluation [6][7][8][9], geophysical prospecting [10], and biomedical engineering [11][12][13][14]. Microwave imaging has also been proposed as a useful tool in wood industry [15].…”
Section: Introductionmentioning
confidence: 99%